2013
DOI: 10.1088/1367-2630/15/2/025017
|View full text |Cite
|
Sign up to set email alerts
|

Super-Gaussian transport theory and the field-generating thermal instability in laser–plasmas

Abstract: Inverse bremsstrahlung (IB) heating is known to distort the electron distribution function in laser-plasmas from a Gaussian towards a super-Gaussian, thereby modifying the equations of classical transport theory (Ridgers et al 2008 Phys. Plasmas 15 092311). Here we explore these modified equations, demonstrating that super-Gaussian effects both suppress traditional transport processes, while simultaneously introducing new effects, such as isothermal (anomalous Nernst) magnetic field advection up gradients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Inverse bremsstrahlung heating of plasma results in a super-Gaussian electron distribution [18], which modifies the transport coefficients [21,26,27] and introduces new terms including an anomalous heat flux up a pressure…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inverse bremsstrahlung heating of plasma results in a super-Gaussian electron distribution [18], which modifies the transport coefficients [21,26,27] and introduces new terms including an anomalous heat flux up a pressure…”
mentioning
confidence: 99%
“…Using theory detailed in refs. [21,27], the heat flow can be modified in hydrodynamics codes to include this effect. However, the distribution is not precisely a super-Gaussian [28] due to other effects such as non-locality, magnetic-fields, and collisions and this fix remains an approximation.…”
mentioning
confidence: 99%
“…As part of a recent article (Bissell et al 2013) we discussed how super-Gaussian transport effects arising from strong inverse bremsstrahlung (I.B.) heating can suppress growth-rates of one such candidate, the field-generating thermal instability, which was first reported in 1974 (Tidman & Shanny 1974;Bol'shov et al 1974), and remains an important phenomena in laser-plasma interactions (see, for example, experimental studies of coronal plasmas by Manuel et al (2013) reported earlier this year).…”
Section: Introductionmentioning
confidence: 99%
“…In the first case (i) feedback acts between ∇T e × ∇n e generated field and the consequent crossgradient Righi-Leduc heat-flow q ∧ ∝ b × ∇T e (Haines 1986a;Braginskii 1965;Tidman & Shanny 1974;Bol'shov et al 1974). In the second (ii) it is commonly understood that lateral advection of the field with the diffusive heat-flow q ⊥ ∝ ∇T e via the Nernst effect (Nishiguchi et al 1985;Bissell et al 2013), i.e., with velocity v N ≈ q ⊥ /( 3 2 n e T e ), can lead to exponential compression of the perturbation in B (Brownell 1979;Hirao & Ogasawara 1981). In the absence of hydrodynamic effects, case (i) requires that zeroth-order temperature and density gradients be parallel, i.e., l T l n > 0, where in an x-coordinate aligned geometry the length scales l T and l n may be defined…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation